Characterization of a Cyanobacterial Chloride-pumping Rhodopsin and Its Conversion into a Proton Pump - Hasemi, Takatoshi (J Biol Chem, 2016)
Light-driven ion-pumping rhodopsins are widely distributed in microorganisms and are now classified into the categories of outward H(+) and Na(+) pumps and an inward Cl(−) pump. These different types share a common protein architecture and utilize the photoisomerization of the same chromophore, retinal, to evoke photoreactions. Despite these similarities, successful pump-to-pump conversion had been confined to only the H(+) pump bacteriorhodopsin, which was converted to a Cl(−) pump in 1995 by a single amino acid replacement. In this study we report the first success of the reverse conversion from a Cl(−) pump to a H(+) pump. A novel microbial rhodopsin (MrHR) from the cyanobacterium Mastigocladopsis repens functions as a Cl(−) pump and belongs to a cluster that is far distant from the known Cl(−) pumps. With a single amino acid replacement, MrHR is converted to a H(+) pump in which dissociable residues function almost completely in the H(+) relay reactions. MrHR most likely evolved from a H(+) pump, but it has not yet been highly optimized into a mature Cl(−) pump.